Current status of tropical fruits in India - SINGH, H P; YADAV, I S; UMA, S (The Indian Journal of Agricultural Sciences, 2013)
During the last 5 decades intensification of research resulted in significant changes in tropical fruits. Citrus (Citrus spp) maintained annual growth of 7.7%. It is the third largest fruit crop with tolal production of 2.98 million trom 369 500 ha. Banana (Musa sp) production has heen increased by more than 1000 •. The total production of banana (10 million tonnes) contributes 31% of the total fruit production in India. Papaya (Carica papaya L.) and pineapple [Ananas COmOsus (L.) Merr.] also showed signiticant increase in their respective area and production. Papaya is grmvn all 45 200 ha land with estimated production of 0.905 million tonnes. Productivity ranges up to 40 tonnes/ha. with national average or 19.85 tonnes/ha. The pineapple occupies an area of 54 500 ha with estimatated production of 786 no tonnes. having productivity of 14.41 tonnes/ha. Sapota [Manilkara achras (Mill.) Forsberg.] has now become choice crop in dry region. Sapota showed unprecedented increase in area and production due to its wide adaptahility and growing demand for fruits. Presently it is cultivated in 40 In ha with totol production of 571 542 tonnes. Current status of theHe tropical fruits is reviewed in this article.